Accuracy of the defining characteristics of the nursing diagnosis for fatigue in women under radiotherapy - Suzy Ramos Rocha; Míria Conceição Lavinas Santos; Marcos Venícios de Oliveira Lopes; Andrea Bezerra Rodrigues; Vanessa Emille Carvalho de Sousa; Caroline Batista de Queiroz Aquino; Cláudia Rayanna Silva Mendes
ABSTRACT Objective: To evaluate the accuracy of the defining characteristics of the nursing diagnosis for "fatigue in women with breast cancer under radiotherapy". Method: Study of diagnostic accuracy, with cross-sectional design, performed in 130 women with breast cancer under radiation treatment. A data collection instrument was used to evaluate clinical socio-demographics and to investigate the presence or absence of defining characteristics for fatigue. The latent class analysis model was applied to assess accuracy measurements of the characteristics identified. Results: Fatigue diagnosis was present in 21.9% of the women. The characteristic which showed the highest sensitivity was "Impaired capacity in maintaining the usual level of physical activity", while "Impaired capacity in maintaining usual routines" and "Lack of interest about the surrounding environment" presented greater specificity. Conclusion: Accurate diagnostics allow devising an action plan directed to the patients' real needs.